BILATERAL PUTAMEN HAEMORRHAGIC NECROSIS DUE TO METHANOL INTOXICATION: Methanol Intoxication - Ibrahim, Muhammad Imran; Azam, Khalid; Qayyum, Abdul; Zeeshan, Akhtar; Shafi, Nouman; Munawar, Shahzad (Pakistan Armed Forces Medical Journal, 2015)
INTRODUCTIONMethanol toxicity presents as an emergency because of its preferential and early involvement of basal ganglia and optic pathways. Although history might help in early clinical diagnosis but here we present a rare case of chronic alcoholic patient, who presented as a diagnostic dilemma from a local hospital.